LEGAL PROTECTION FOR DEBTORS ACTING IN GOOD FAITH IN FULFILLING OBLIGATIONS TO UNIDENTIFIED CREDITORS - Hardiyansyah, Tendri; Tjempaka, Tjempaka (Awang Long Law Review, 2025)
The transfer of receivables (cession) in mortgage loan agreements without prior notice to the debtor has led to legal uncertainty and poses a risk of harm to debtors acting in good faith. This study aims to analyze the legal standing of debtors in cases of cession conducted without notification, as well as to identify forms of legal protection available to such debtors. The research adopts a normative juridical approach, relying on the analysis of statutory regulations and a case study of the Tangerang District Court Decision No. 1238/Pdt.G/2022/PNTng. The findings indicate that although Article 613 of the Indonesian Civil Code requires notification to the debtor in the event of cession, the absence of sanctions for creditors who fail to comply allows the practice of transferring receivables without debtor notification to persist. As a result, debtors are often exposed to the risks of double payment or being considered in default by the new creditor. This research recommends strengthening regulations concerning the mandatory notification of cession and encouraging the active role of financial authorities in ensuring transparency and protection for debtors. The implications of this study underscore the need for legal reform to establish a fairer and more legally certain system for the transfer of receivables.